VIRTUAL MOUSE WITH HAND GESTURE RECOGNITION BASED ON HAND LANDMARK MODEL FOR POINTING DEVICE - Jeffri Dian Asmoro; Achmad Teguh Wibowo; Mujib Ridwan (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: Technology is growing rapidly and has become one of the human needs that must be owned to solve the problems being faced. The development of touchless input devices or hand gesture recognition using a camera is a form of machine learning. Gestures can define as physical movements of the hands, arms, or body as expressive messages, besides that this hand gesture system can explain the contents of commands that have meaning. In this research, a virtual mouse system will be developed using hand gesture recognition based on the hand landmark model for pointing devices. The resulting application can be run on a desktop device using a webcam. The results of the tests carried out to analyze the implementation of the hand landmark model into the system show that the average system accuracy reaches 96% and the speed reaches 0.05 seconds.            Keywords: hand gesture recognition, hand landmark models, machine learning, virtual mouse  Abstract: Teknologi semakin pesat dan sudah menjadi salah satu kebutuhan manusia yang harus dimiliki untuk menyelesaikan permasalahan yang sedang dihadapi. Perkembangan piranti masukan tanpa sentuhan atau hand gesture recognition menggunakan kamera adalah salah satu bentuk dari machine learning. Gestur mampu mendefinisikan sebagai gerakan fisik dari tangan, lengan, maupun badan sebagai pesan yang ekspresif, selain itu sistem gestur tangan ini mampu menjelaskan isi perintah yang memiliki arti. Dalam penelitian ini akan dikembangkan sebuah sistem virtual mouse menggunakan hand gesture recognition berbasis hand landmark model untuk pointing device. Aplikasi yang dihasilkan dapat dijalankan pada perangkat desktop dengan menggunakan webcam. Hasil dari pengujian yang dilakukan untuk menganalisa penerapan hand landmark model kedalam sistem menunjukkan rata-rata akurasi sistem mencapai 96% dan kecepatan mencapai 0.05 second.           Keywords: hand gesture recognition, hand landmark models, machine learning, virtual mouse